Pattern-based Business Model Development for Cyber-Physical Production Systems - Rudtsch, Vinzent; Gausemeier, Jürgen; Gesing, Judith; Mittag, Tobias; Peter, Stefan

Virtual Reality based Conjoint Analysis for Early Customer Integration in Industrial Product Development - Backhaus, Klaus; Jasper, Jonas; Westhoff, Katharina; Gausemeier, Jürgen; Grafe, Michael; Stöcklein, Jörg

Conceptual Design of a Self-Optimising Production Control System - Mittag, Tobias; Gausemeier, Jürgen; Gräßler, Iris; Iwanek, Peter; Köchling, Daniel; Petersen, Marcus
Current production control systems cannot react appropriately to unknown situations (e.g. the dispatch of rush jobs). They are only able to react on known situations with a predefined behaviour. In this paper the paradigm of self-optimisation will be transferred to the production control level by using a procedure model to design a self-optimising production control system. The production control is then able to react autonomously on changing operational conditions and to deduce new reaction strategies for occurring faults or disturbances. A rule based decision model is the core of the conceptual design. It is based on known and possible future faults and deducts reaction strategies. Simultaneously to them, a simulation model will be proposed, that simulates and evaluates suitable strategies.

Pr {\ "a} ventive product protection - a holistic approach for ü r threat analysis - Eckelt, Daniel; Altemeier, Katharina; Kliewe, Daniel (Industry Management)

Using the scenario technique for diversification opportunities - systematic identification of search fields at SKF GmbH - G {\ "o} tz, Johannes; Schulz, Ingo; Wiederkehr, Olga (10th Symposium on Foresight and Technology Planning)

Systematics for the development of business models in product creation - K {\ "o} ster, Oliver

System for planning cross-industry innovations - Echterhoff, Niklas

A Design Framework for Developing a Reconfigurable Driving Simulator - Hassan, Bassem

Process for developing business model-oriented diversification strategies - Lehner, Markus

Introduction to Self-optimization - Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter (Design Methodology for Intelligent Technical Systems)